2019
DOI: 10.1038/s41433-019-0428-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of presumed trematode-induced granulomatous anterior uveitis among children in rural areas of Egypt

Abstract: Purpose The purpose of this study is to evaluate the efficacy of systemic antiparasitic medications alone or in combination with surgical aspiration in management of presumed trematode-induced anterior uveitis in children. Patients and methods Prospective case series. Children who presented with anterior chamber (AC) granuloma were included in the study. All patients received antiparasitic treatment and after 2 weeks; patients were divided based on their clinical improvement in terms of the baseline granuloma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Similar cluster was reported from different geographical locations along the basin of river Nile by R.M. Amin et al from Egypt with granulomatous anterior uveitis after swimming in the river [8][9] . Here again the etiological agent was proven by molecular diagnostics to be trematode.…”
Section: Epidemiologysupporting
confidence: 87%
“…Similar cluster was reported from different geographical locations along the basin of river Nile by R.M. Amin et al from Egypt with granulomatous anterior uveitis after swimming in the river [8][9] . Here again the etiological agent was proven by molecular diagnostics to be trematode.…”
Section: Epidemiologysupporting
confidence: 87%
“…The belief that prevailed in the earlier periods and the related research studies indicated a stage of one of the atworms as the cause of these ocular infections [3][4][5][6]. Many Egyptian specialists in collaboration with their scienti c teams accepted such assumption and recommended antiparasitic drugs alone, in combination with surgical aspiration, or other interventions in the management of such presumed trematode-induced anterior uveitis in children in different governorates Amin et al [3] in Alexandria, El Nokrashy et al [7] in Mansoura, Sadek et al [8] in Al-Fayoum. The same concept was followed in India [4,6].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, prompt treatment is crucial for a favorable outcome. Current treatment modalities used include the following: (1) corticosteroids either topical, regional, or systemic; [8] (2) antimicrobial medications with controversial results; [9] (3) laser photocoagulation; [20] (4) surgical treatment for cases not responding to conservative treatment [1,8,9].…”
Section: Discussionmentioning
confidence: 99%